Death Receptor 6 is Epigenetically Silenced by Histone Deacetylation in Endometriosis and Promotes the Pathogenesis of Endometriosis. (13th September 2013) - Kai, Kentaro; Nasu, Kaei; Kawano, Yukie; Aoyagi, Yoko; Tsukamoto, Yoshiyuki; Hijiya, Naoki; Abe, Wakana; Okamoto, Mamiko; Moriyama, Masatsugu; Narahara, Hisashi
<x xml:space="preserve">Abstract</x> Problem The purpose of this study is to evaluate the involvement of death receptor (DR) 6 in the pathogenesis of endometriosis. Methods of study Endometriotic cyst stromal cells (ECSCs) and normal endometrial stromal cells (NESCs) were isolated from ovarian endometriotic tissues and the eutopic endometrial tissues, respectively. The effect of valproic acid (VPA) on the DR6 expression in ECSCs was examined. The roles of DR6 in NESC proliferation and apoptosis were investigated with DR6 siRNA transfection. The distribution of DR6 protein in ovarian endometriotic tissues and normal proliferative‐phase endometrium was examined by immunohistochemistry. The expression of DR6 mRNA and protein in ECSCs and NESCs was also examined. Results Death receptor 6 expression was attenuated in ECSCs and in endometriotic tissues, and its expression was upregulated by VPA stimulation. VPA treatment resulted in an accumulation of acetylated histone H4 in the promoter region of the DR6 gene. DR6 knockdown directed the stimulation of cell proliferation and the resistance to apoptosis in NESCs. Conclusion The present findings suggested that DR6 is involved in the pathogenesis of endometriosis by creating the proliferative and anti‐apoptotic characteristics of endometriosis. The results also suggest that histone deacetylase inhibitors are promising agents for the treatment of endometriosis.